HEURISTICS AND SKEPTICISM: DO RED FLAGS SPEAK LOUDER IN FRAUD DETECTION? - Saputra, Dian; Abrar, Abrar; Nawanir, Gusman; Sinaga, Ferdinand IP; pangestu, Galih gestri (Faculty of Economics and Business University of Mataram, 2025)
This study is motivated by the recurring inability of auditors to detect fraud, despite the prevalence of financial scandals that have drawn significant public and professional scrutiny. In response to this concern, the research investigates the influence of heuristics, fraud risk indicators (commonly referred to as red flags), and professional skepticism on auditors’ effectiveness in identifying fraudulent activity. Particular attention is given to professional skepticism as a potential moderating factor in these relationships. A cross-sectional quantitative approach was employed, involving survey data collected from 143 auditors working in public accounting firms across Indonesia. The data were analyzed using partial least squares structural equation modeling (PLS-SEM). The results indicate that heuristics, red flags, and professional skepticism each exert a positive effect on auditors’ fraud detection capabilities. Moreover, the analysis reveals that professional skepticism amplifies the impact of heuristics but does not significantly moderate the relationship between red flags and fraud detection. These findings underscore the importance of audit training that cultivates both intuitive and analytical reasoning, as well as the need for regulatory structures that reinforce the consistent application of professional skepticism in practice.